Influence of intensive cycling training on heart rate variability during rest and exercise - Leicht, A. S.; Allen, G. D.; Hoey, A. J. (Canadian Journal of Applied Physiology, 2003)
The current study examined whether changes in heart rate variability (HRV) following intensive cycling training contribute to the mechanism of training-induced bradycardia. Thirteen healthy untrained subjects, ages 18-27 years, underwent recordings of heart rate (HR) and VO2max before and after 8 weeks of cycling, 25-60 min/day, 5 days/week at >80% maximum HR (HRmax). Heart rate recordings were obtained during supine rest and submaximal exercise and were analysed for the following components of HRV: low frequency (LF, 0.041-0.15 Hz); high frequency (HF, 0.15-0.40 Hz); LF/HF ratio and total power (TP, 0-0.40 Hz). At posttraining, VO2max was significantly increased while HR was significantly reduced at rest and all absolute exercise work rates. Training-induced lower HR was accompanied by significantly greater HF and TP during rest as well as LF, HF, and TP during all absolute exercise work rates. Posttraining HR and the majority of HRV measures were similar to pretraining values at the same relative exercise intensity (% HRmax). These results indicated that 8 weeks of intensive cycling training increased HRV and cardiac vagal modulation during rest and absolute exercise work rates but had little effect during relative exercise work rates. Increased vagal modulation resulting from intensive exercise training may contribute to the mechanism of training-induced bradycardia.